Pengaruh literasi digital berbasis etnosains terhadap hasil belajar IPAS SD Negeri 225 Palembang - Fatmawati Dwi Khairani; Kiki Aryaningrum; Sunedi (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to determine the effect of digital literacy based on ethnoscience through the linktree platform on the learning outcomes of class V students of SDN 225 Palembang with the material Indonesiaku Kaya Hayatinya. This type of research is a quantitative experimental study with a posttest-only control design. The research sample consisted of two classes, namely class V A and class V B, with a total of 64 students. Data collection techniques used tests and documentation. The results showed that in the control class the average posttest score was 60.62. These data indicate that the learning outcomes of the control class have not met the minimum completeness criteria, which is 75. While in the experimental class, the average posttest score was 70, which means that the learning outcomes of the experimental class have met the minimum completeness criteria. The normality test showed that the posttest data of the two groups of students, namely the control class and the experimental class, had a normal distribution with a significance value of 0.295 in the control class and 0.295 in the experimental class. The results of the homogeneity test showed a value of 0.788, which is greater than 0.05, so it can be declared homogeneous. In the hypothesis test with the independent sample t-test, a significance value (2-tailed) of 0.020 was obtained, which is smaller than 0.025. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Thus, it can be concluded that there is an influence of the use of ethnoscience-based digital literacy through the linktree platform on the science learning outcomes of grade V students of SDN 225 Palembang.